2008
DOI: 10.1086/591093
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Type‐1 Fimbriae by NonpathogenicEscherichia coli83972 Results in an Increased Capacity for Catheter Adherence and Bacterial Interference

Abstract: Background In vitro, urinary catheter colonization by avirulent Escherichia coli 83972 impedes subsequent catheter colonization by a variety of uropathogenic organisms. However, E. coli 83972 shows a low efficacy of adherence to silicone urinary catheter material, possibly because the fim operon encoding adhesive type 1 fimbriae is incomplete. We hypothesized that improving the catheter adherence of E. coli 83972 would improve its bacterial interference properties. Methods We created adhesive mutants by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Type 1 fimbriae, as determined by yeast agglutination, were expressed by the majority of the ABU and CA-ABU E. coli strains. This fimbrial type, unlike P fimbriae, is associated with catheter colonization and persistence in the catheterized urinary tract (28,41). Furthermore, the introduction of a plasmid containing type 1 fimbrial genes increased catheter adherence of ABU strain 83972 up to 100-fold and improved its ability to prevent colonization by pathogenic E. coli (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 fimbriae, as determined by yeast agglutination, were expressed by the majority of the ABU and CA-ABU E. coli strains. This fimbrial type, unlike P fimbriae, is associated with catheter colonization and persistence in the catheterized urinary tract (28,41). Furthermore, the introduction of a plasmid containing type 1 fimbrial genes increased catheter adherence of ABU strain 83972 up to 100-fold and improved its ability to prevent colonization by pathogenic E. coli (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms of biofilm formation by E. coli in the catheterized urinary tract are not fully understood, surface adhesins such as type 1 fimbriae, type 3 fimbriae, and curli have been shown to contribute to biofilm growth (28,29,41,43). In contrast, ABU E. coli strains are often associated with poor epithelial cell adhesion properties, and thus, the role of biofilm growth in colonization by these strains is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo we have observed that the adherence of E. coli 83972 to unmodified silicone urinary catheters is low in comparison to the adherence of urinary pathogens (1719). Furthermore, we have demonstrated that we can increase adherence of E. coli 83972 to catheter surfaces by manipulating expression of type 1 fimbriae, and increased surface adherence leads to increased ability to block pathogen adherence to urinary catheters (17).…”
Section: Introductionmentioning
confidence: 93%
“…Both the Escherichia coli 83972 expressing type 1 fimbriae ( fim+ E. coli 83972, strain HU2545) 35 and the challenge pathogenic bacteria, Enterococcus faecalis 210, were provided by Dr. Barbara W. Trautner (Baylor College of Medicine). This strain of E. faecalis was transformed with pMB158GFP to express green fluorescence protein (GFP) that can be observed by fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%